Comprehensive analysis for modified particle swarm optimisation with PD controllers. (1st January 2011) - Jie, Jing; Wang, Wanliang
Inspired by the information prediction existing in the nature intelligent agents, the author has developed a modified particle swarm optimisation (PSO) with a forward PD controller (SPSO-FWPD) earlier. Comprehensive analysis for the model is provided in the paper, including its stabilisation, convergence and dynamic behaviour. Later, another modified PSO with a feedback PD controller (SPSO-FBPD) is presented accompanying some analysis. The introductions of different PD controllers develop the standard PSO (SPSO) with information prediction capability, which can guide the particle to respond to the change of their exemplars correctly and rapidly, and greatly contributes to a successful global search. The proposed methods provide some new ideas for the improvement of SPSO, and are compared with SPSO based on some numerical optimisation simulations. The relative experimental results show SPSO with different PD controller performs better than SPSO on the complex optimisation problems.